2013
DOI: 10.1007/s11033-013-2777-y
|View full text |Cite
|
Sign up to set email alerts
|

Y chromosome diversity and paternal origin of Chinese cattle

Abstract: To determine the Y chromosome genetic diversity and paternal origin of Chinese cattle, 369 bulls from 17 Chinese native cattle breeds and 30 bulls from Holstein and four bulls from Burma were analyzed using a recently discovered USP9Y marker that could distinguish between taurine and indicine cattle more efficiently. In total, the taurine Y1, Y2 haplogroup and indicine Y3 haplogroup were detected in 7 (1.9 %), 193 (52.3 %) and 169 (45.8 %) individuals of 17 Chinese native breeds, respectively, although these f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Subsequent investigations using Y-SNPs and Y-STRs further confirmed that Y2 dominates the north (91.4%) and Y3 in the south of China (90.8%) . All the three haplogroups described in cattle (Y1, Y2 and Y3) have also been detected in Southwest Asia, where Y3 is found to be limited in Bos indicus of Indian subcontinent and China (Edwards et al, 2011;Chang et al, 2011;Zhang et al, 2013;Li et al, 2013). In the present investigation three haplogroup (Y1, Y2 and Y3) have been detected (Table 3).…”
Section: Resultssupporting
confidence: 73%
“…Subsequent investigations using Y-SNPs and Y-STRs further confirmed that Y2 dominates the north (91.4%) and Y3 in the south of China (90.8%) . All the three haplogroups described in cattle (Y1, Y2 and Y3) have also been detected in Southwest Asia, where Y3 is found to be limited in Bos indicus of Indian subcontinent and China (Edwards et al, 2011;Chang et al, 2011;Zhang et al, 2013;Li et al, 2013). In the present investigation three haplogroup (Y1, Y2 and Y3) have been detected (Table 3).…”
Section: Resultssupporting
confidence: 73%
“…Several investigations of cattle CNVs have been conducted, focusing mostly on breed-specific patterns of CNV ( Bae et al 2010 ; Fadista et al 2010 ; Liu et al 2010 ; Hou et al 2011 ; Stothard et al 2011 ; Zhan et al 2011 ; Bickhart et al 2012 ; Jiang et al 2012 , 2013 ). However, modern breeding practices commonly used in the cattle industry include artificial insemination and hybridization of breeds (thereby introducing more variation in CNVs), for example, when importing foreign excellent cattle sperm for insemination of Chinese cows ( Li, Xie, et al 2013 ). This highlights the necessity for additional, comparative investigations of lineage-specific patterns of CNVs.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of Y-chromosome SNPs identified three haplotypes, namely Y 1 (taurine origin), Y 2 (taurine) and Y 3 (indicine) ( Götherström et al 2005 ), and subsequent investigations using Y-SNPs and Y-STRs confirmed that Y 2 dominated in the north (91.4%) and Y 3 in the south of China (90.8%) ( Li, Zhang, et al 2013 ). A number of studies also suggest that hybridization and introgression of taurine and indicine cattle occurred, especially in central parts of China, but inferences were mostly made on the basis of mtDNA and Y-chromosomal information only ( Lai et al 2006 ; Jia et al 2010 ; Li, Xie, et al 2013 ). Y-chromosomes and mtDNA, however, generally lack recombination and thus, are of limited use to unravel patterns of genome evolution after hybridization and artificial selection ( McTavish et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Import of foreign cattle from countries such as the Netherlands and Sweden, especially bulls, increased in Finland during the 18 th — 19 th centuries [ 45 ]. In contemporary Taurus cattle populations, haplotype Y2 dominates in almost the whole Eurasian region [ 23 , 46 , 47 ], with the exception of Western and Northern Europe [ 23 ]. The present-day European Y-chromosomal distribution has been taken as evidence of two different expansions of dairy cattle to the Nordic countries [ 23 ].…”
Section: Discussionmentioning
confidence: 99%